The Effects of Lycopene and Tomato Consumption on Cardiovascular Risk Factors in Adults: A Grade Assessment Systematic Review and Meta-analysis - Zamani, Mohammad; Behmanesh Nia, Farimah; Ghaedi, Kimia; Mohammadpour, Saba; Amirani, Niusha; Goudarzi, Kian; Kolbadi, Kosar S. H.; Ghanavati, Matin; Ashtary-larky, Damoon (Current Pharmaceutical Design, 2023)
Background: In recent times, modifying dietary habits to control cardiovascular risk factors has gained significant attention. However, previous studies have yielded inconsistent results regarding the effects of lycopene and tomato consumption on cardiovascular risk factors. Objective: The objective of this study was to assess the impact of consuming lycopene and tomatoes on various cardiovascular risks factors such as lipid profile, glycemic control markers, blood pressure, inflammation, oxidative stress, and body weight. Methods: A systematic literature search was carried out using electronic databases, including PubMed, Web of Science, and Scopus, up to November 2022 to identify eligible Randomized Control Trials (RCTs) evaluating the effect of lycopene and tomato consumption on cardiovascular risk factors. Heterogeneity tests of the selected trials were performed using the I2 statistic. Random effects models were assessed based on the heterogeneity tests, and pooled data were determined as the weighted mean difference (WMD) with a 95% confidence interval (CI). Results: Out of 27,438 records initially identified, a total of 34 studies met the eligibility criteria and were included in this meta-analysis. The results showed that lycopene consumption was associated with a significant reduction in malondialdehyde (MDA) levels, indicating a potential benefit in reducing oxidative stress. However, lycopene and tomato consumption did not have significant effects on other cardiovascular risk factors such as triglycerides (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), fasting blood glucose (FBG), systolic blood pressure (SBP), diastolic blood pressure (DBP), Intercellular Adhesion Molecule 1 (ICAM-1), c-reactive protein (CRP), interleukin 6 (IL-6), tumor necrosis factor α (TNF-α), body weight, and body mass index (BMI). Conclusion: Overall, the findings showed that lycopene and tomato consumption did not affect cardiovascular risk factors. However, lycopene supplementation may result in a significant improvement in MDA levels. With the view to confirming these results, further studies with long-term duration and different doses are needed.
Keywords: oxidative stress